Low voltage-activated calcium channels gate transmitter release at the dorsal root ganglion sandwich synapse - Rozanski, Gabriela M (Blackwell Science Inc, 2013)
A subpopulation of dorsal root ganglion (DRG) neurons are intimately attached in pairs and separated solely by thin satellite glial cell membrane septa. Stimulation of one neuron leads to transglial activation of its pair by a bi-, purinergic/glutamatergic synaptic pathway, a transmission mechanism that we term sandwich synapse (SS) transmission. Release of ATP from the stimulated neuron can be attributed to a classical mechanism involving Ca(2+) entry via voltage-gated calcium channels (CaV) but via an unknown channel type. Specific blockers and toxins ruled out CaV1, 2.1 and 2.2. Transmission was, however, blocked by a moderate depolarization (−50 mV) or low-concentration Ni(2+) (0.1 mm). Transmission persisted using a voltage pulse to −40 mV from a holding potential of −80 mV, confirming the involvement of a low voltage-activated channel type and limiting the candidate channel type to either CaV3.2 or a subpopulation of inactivation- and Ni(2+)-sensitive CaV2.3 channels. Resistance of the neuron calcium current and SS transmission to SNX482 argue against the latter. Hence, we conclude that inter-somatic transmission at the DRG SS is gated by CaV3.2 type calcium channels. The use of CaV3 family channels to gate transmission has important implications for the biological function of the DRG SS as information transfer would be predicted to occur not only in response to action potentials but also to sub-threshold membrane voltage oscillations. Thus, the SS synapse may serve as a homeostatic signalling mechanism between select neurons in the DRG and could play a role in abnormal sensation such as neuropathic pain.